Clubfoot : a comprehensive approach - Mittal, R. L. (Rattan Lal) (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
Clubfoot is a common deformity but remains unsolved. Detailed epidemiology has been described to assess the socio-economic impact. All corrective methods are enumerated, highlighting their efficacy and pitfalls. The importance of each clubfoot case being different and the means of dealing it is emphasized upon. This is a comprehensive book on Clubfoot with the types and their mode of treatment extensively discussed. Also, Clubfoot differences during birth, additional birth defects, weight bearing effect with age, previous scars, trauma and other complications are covered. Key Features A comprehensive book on Clubfoot Explained the different kinds of clubfoot Evidence based description of each clubfoot being different Updated with the latest treatment techniques Comparative analysis of various treatment options
Epidemiology : nomenclature, classifications, definitions -- Review of literature -- Pathoantomoy of clubfoot -- Triple surgical techniques -- Future in clubfoot.
OCLC-licensed vendor bibliographic record.
Keywords: Clubfoot; Clubfoot -- Treatment; MEDICAL / Surgery / General